LEGAL ASPECTS OF THE STUDY OF THE WORK “THE LAWS OF TIMUR” - Salahiddinov Javahir Bakhtiyar ugli (Scholar Express Journals, 2022)
The article reflects on the legal basis of the work of Timur's structures. It presents the source characteristics of legal concepts in the management of the important foundations of statehood. In the statehood of Amir Timur, the criterion of the idea of building a fair society is determined
Keywords: : Amir Temur; Malfuzoti Temuri; Voqeati Temuri; Tuzuklari Temur